Ductility and pseudo-ductility of thin ply angle-ply CFRP laminates under quasi-static cyclic loading. (April 2018) - Fuller, J.D.; Wisnom, M.R.
Abstract: The quasi-static loading-unloading performance of thin ply carbon-epoxy [ ± 26 5 ] s, [ ± 27 5 ] s and [ ± 26 5 / 0 ] s laminates is presented. Consistent experimental results allow the reduction in laminate modulus to be evaluated using three different methods: secant modulus of each loading cycle; a secant modulus up to a constant stress, and the initial tangent modulus of reloading. It is shown, via all three methods, that these layups can undergo multiple cyclic loadings and display excellent retention of stiffness. The [ ± 26 5 / 0 ] s layup displays a limited modulus reduction, despite the gradual failure of the 0 ° layers. The [ ± θ 5 ] s specimens do not display any decrease in initial modulus and effectively suppress damage accumulation (shown via X-ray CT imaging), which both suggest that the stress–strain behaviour of these layups is ductile, rather than pseudo-ductile.